PECULIARITIES OF APPLICATION OF PUBLIC-PRIVATE PARTNERSHIP AS A MECHANISM FOR IMPLEMENTATION OF INNOVATION ACTIVITY - Bogdana Vyshnivska; Olena Kireitseva (Three Seas Economic Journal, 2022)
The purpose of the article is the theoretical justification and development of scientific and methodological provisions and practical recommendations for the development of public-private partnership in order to ensure the modernization of the economy on an innovative basis. The methodological basis is the general and special methods: historical method; method of scientific abstraction (in order to generalize the conceptual foundations of the study); methods of analysis and synthesis - in the study of the structure of the innovation system in public-private partnership; induction and deduction (to study approaches to the definition of innovation in public-private partnership); method of comparison (in order to justify the application of foreign experience of innovation in public-private partnership in our country); methods of grouping and systematization (in order to classify, identify factors of innovation development, factors of formation of the national innovation system); statistical methods (in order to analyze the dynamics of innovation in the economy of Ukraine, trends in the formation of innovation infrastructure). The results of the study showed that most accurately reproduces the meaning of the concept of public-private partnership, when public relations are actively involved in the relationship with the private sector, emphasizing the public focus. However, in countries with economies in transition, where institutions of civil society are underdeveloped, the term "public-private partnership" is most often used. Since the initiator of the vast majority of public-private partnership projects, the main actor is the state. The problems of formation and development of public-private partnership are currently paid considerable attention in foreign studies. The world practice has accumulated considerable experience in the implementation of public-private partnership in various areas and spheres of activity. In many countries, public-private partnerships have proven effective in modernizing the economy and have long been a domestic policy priority. The practical significance of the results is that the provisions, conclusions and recommendations have a practical orientation and can be used to improve the efficiency of regulation of innovation processes in terms of public-private partnership. Value/originality. The peculiarity of the proposed definition is that public-private partnership is an effective tool of state regulation only if conditions of competition between private sector entities for the right to participate in a particular PPP project are created.